Comparison of indoor air quality (IAQ) in a selected sample of linked and detached homes in the Klang Valley, Malaysia / Shaheera Shahrani - Shahrani, Shaheera (2007)
Indoor air pollution is consistently reported to be two to five times- and occasionally up to 1,000-times higher than outdoor levels (Arant, 2005; Eek, 2005; Soper, 2005). This is alarming considering that the majority of people tend to spend an average of 70% to 96% of their time in indoor environments (Arant, 2005; cited in ARPDC, 2005a; ARPDC, 2005b), of which approximately 60% to 75% of the time is spent at home (CARB, 2005; cited in ARPDC, 2005a; ARPDC, 2005b). For these reasons, when compared to other threats to human health and well-being, the United States Environmental Protection Agency and its Science Advisory Board consistently rank poor indoor air quality (IAQ) amongst the top five most urgent environmental risks to public health and well-being (Arant, 2005; cited in 3M & ALA, 2004; cited in Paras, 2004); the World Health Organization (WHO) ranks indoor air pollution as one of the top five risk factors contributing to the global burden of disease (cited in Eek, 2005); and the World Bank ranks indoor air pollution in developing countries as one of the four most critical global environmental concerns (cited in ITERI, 2002; cited in Unobe, 2003).